2014
DOI: 10.3390/cells3020304
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Activation of Receptor Tyrosine Kinases: Monomers or Dimers

Abstract: Receptor tyrosine kinases (RTKs) play essential roles in cellular processes, including metabolism, cell-cycle control, survival, proliferation, motility and differentiation. RTKs are all synthesized as single-pass transmembrane proteins and bind polypeptide ligands, mainly growth factors. It has long been thought that all RTKs, except for the insulin receptor (IR) family, are activated by ligand-induced dimerization of the receptors. An increasing number of diverse studies, however, indicate that RTKs, previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
126
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(133 citation statements)
references
References 212 publications
(311 reference statements)
4
126
0
3
Order By: Relevance
“…In a manner similar to many type-1 transmembrane domain receptors [44, 6971] , APP can form homodimers as well as heterodimers by interacting with its homologues or putative ligands. Dimerization of APP is mediated by motifs present in the extracellular and the transmembrane domains of the protein.…”
Section: The Role Of App Subdomains In Dimerization Processmentioning
confidence: 99%
“…In a manner similar to many type-1 transmembrane domain receptors [44, 6971] , APP can form homodimers as well as heterodimers by interacting with its homologues or putative ligands. Dimerization of APP is mediated by motifs present in the extracellular and the transmembrane domains of the protein.…”
Section: The Role Of App Subdomains In Dimerization Processmentioning
confidence: 99%
“…Like many other type-1 transmembrane receptors such as receptor tyrosine kinases and cytokine receptors (116, 117), rGCs have a homo- or heterodimeric structure in the absence of bound ligand (26, 118–120). The ECD of rGCs often encodes regions that recognize extracellular cues such as peptides or ions.…”
Section: Mechanism Of Activation Of Rgcsmentioning
confidence: 99%
“…However, numerous studies have demonstrated that prior to ligand binding, EGFR exists in dimeric, yet inactive, form at the cell surface [8,36]. By using different chemical cross-linkers from those previously employed, it is found that EGFR exists in dimeric form prior to ligand binding [37,38].…”
Section: Egfr Has a Dimeric Structurementioning
confidence: 99%
“…The receptor is activated by binding of various ligands including epidermal growth factor (EGF), transforming growth factor α (TGFα), amphiregulin (AREG), epigen, β-cellulin, heparin-binding EGF (HB-EGF) and epiregulin [6,7]. EGFR is a singlepass transmembrane protein, consisting of an extracellular domain, a transmembrane domain, a juxtamembrane (JM) segment, a kinase domain, and a C-terminal regulatory tail ( Figure 1) [8,9]. Upon ligand binding, the C-terminal tail becomes tyrosinephosphorylated, and mediates interactions between the receptor and downstream effectors such as Shc1 and Grb2 [10].…”
Section: Introductionmentioning
confidence: 99%